2014
DOI: 10.1002/chem.201405123
|View full text |Cite
|
Sign up to set email alerts
|

Biological Components and Bioelectronic Interfaces of Water Splitting Photoelectrodes for Solar Hydrogen Production

Abstract: Artificial photosynthesis (AP) is inspired by photosynthesis in nature. In AP, solar hydrogen can be produced by water splitting in photoelectrochemical cells (PEC). The necessary photoelectrodes are inorganic semiconductors. Light-harvesting proteins and biocatalysts can be coupled with these photoelectrodes and thus form bioelectronic interfaces. We expand this concept toward PEC devices with vital bio-organic components and interfaces, and their integration into the built environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…16,[74][75][76][77] Only a handful of MOFs have been reported that are capable of performing electrocatalytically driven water oxidation and reduction. Simplistically speaking, an electrocatalytic system eliminates many of the complexities of the Z-scheme, because the cathode (reducing electrode) and the anode (oxidising electrode) mediate direct reduction of H + into dihydrogen and oxidation of OH À into dioxygen respectively, when a sufficient overpotential is applied.…”
Section: Mof Supported Electrocatalytically Driven Water Splittingmentioning
confidence: 99%
“…16,[74][75][76][77] Only a handful of MOFs have been reported that are capable of performing electrocatalytically driven water oxidation and reduction. Simplistically speaking, an electrocatalytic system eliminates many of the complexities of the Z-scheme, because the cathode (reducing electrode) and the anode (oxidising electrode) mediate direct reduction of H + into dihydrogen and oxidation of OH À into dioxygen respectively, when a sufficient overpotential is applied.…”
Section: Mof Supported Electrocatalytically Driven Water Splittingmentioning
confidence: 99%
“…Indirect photochemical reactions are initiated by substances that absorb radiation and subsequently facilitate other reactions that do not involve the original light-absorbing substance [ 42 ]. For example, excited electrons and holes can be indirectly generated in semiconductors by light of lower energy than the band gap: the semiconductor itself does not absorb this light, but another substance (possibly even another semiconductor) that does absorb this light may be excited, and if this substance is in contact with the semiconductor and has appropriate energy levels, electrons can then be transferred between the excited substance and the semiconductor [ 48 , 68 , 79 – 81 ] (Fig. 3 d).…”
Section: Classification Of Photogeochemical Reactionsmentioning
confidence: 99%
“…The study of photogeochemistry, while purely chemical in nature, may even venture into the domain of biology and identify more of the ways in which compounds derived from living organisms can influence abiotic photochemistry [e.g., 81 ], as well as more of the unique relationships between photochemical reactions and biological metabolism known as photobiocatalysis [ 147 – 149 ].…”
Section: Experimental Approachesmentioning
confidence: 99%
“…These photons have deep penetration and therefore can generate holes beyond the depletion layer; hence they recombine fast with the electrons before they arrive to the surface. The performance of pristine hematite can be improved by increasing the semiconductor -electrolyte interface area via nanostructuring [7,39,46], cation doping [43], or by surface functionalization with proteins [8,9,21,28,39,40] which can enhance electron injection into the conduction band.…”
Section: Introductionmentioning
confidence: 99%